PENGARUH ARUS KAS, STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP HARGA SAHAM DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA SEKTOR PARIWISATA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Aminah, Riskil; Sari, Lita Permata; Minullah, Minullah (Fakultas Ekonomi dan Bisnis, 2024)
Tourism sector companies play a significant role in the economy and represent a major source of state revenue. Tourism can be developed as a source of income, both for regional revenue and for the surrounding community. The purpose of this study is to determine the significance of the influence of cash flow, capital structure, and company size on stock prices through profitability. This study employs both descriptive and quantitative research methods. The population consists of 50 tourism sector companies listed on the Indonesia Stock Exchange for the 2020–2023 period. The sampling technique used in this study is purposive sampling. Data analysis and hypothesis testing were conducted using the Partial Least Squares - Structural Equation Modeling (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application show that cash flow has a positive but insignificant effect on profitability, capital structure has a positive but insignificant effect on profitability, company size has a negative and significant effect on profitability, cash flow has a negative but insignificant effect on stock price, capital structure has a significant positive effect on stock price, company size has a positive but insignificant effect on stock price, profitability has a positive but insignificant effect on stock price, cash flow has a positive but insignificant effect on stock price through profitability, the capital structure has a positive but insignificant effect on stock price through profitability, and company size has a negative but insignificant effect on stock price through profitability.